CORRELATION BETWEEN KNOWLEDGE OF SEXUALLY TRANSMITTED INFECTIONS AND PREVENTION BEHAVIOR OF STIS TRANSMISSION AMONG NURSING STUDENTS - Puspitasari, Syahrani; Rahmawati, Nadia; Maulana, M. Ali (Journal of Maternity Care and Reproductive Health, 2024)
Sexually Transmitted Infections (STIs) are diseases that can be transmitted through sexual intercourse with multiple partners, either vaginally, orally, or anally. Infected partners can also transmit STIs to their partners. In 2023, STI cases in Pontianak City will reach 220 cases. In Indonesia, young men and women aged 15 to 24 years have relatively low knowledge about STIs, and insufficient knowledge increases the risk of unsafe sexual behavior.This study aims to determine the correlation between the level of knowledge about STIs and behavior in preventing STI transmission. This research is quantitative using a correlational and cross-sectional design. The sampling technique used was total sampling with a population of 92 students of the Class of 2023 Nursing Study Program at Tanjungpura University. The instruments used 2 questionnaires, STI Knowledge and STI Transmission Prevention Behavior. The STI Knowledge questionnaire has a valid test value of 0.361 and a reliability test value of 0,767. In contrast, the STI Transmission Prevention Behavior questionnaire has a valid test value of 0,358 and a reliability test value of 0,777. The analytical method used is the Spearman Rank. The results that the correlation test showed a significant correlation between the level of STI knowledge and STI transmission prevention behavior with a Sig value (2-tailed), namely ρ = 0,039 and correlation coefficient. The positive correlation result was obtained, namely r = 0,216, meaning that the higher the level of STI knowledge, the higher the behavior to prevent STI transmission. It is hoped that this research will be able to change behavior related to STI prevention, starting by increasing knowledge of STIs. Good knowledge can be the basis for information to change behavior in preventing STIs so that good STI prevention behavior can occur. Future researchers are expected to be able to analyze environmental factors and information related to STI prevention or research related to the same topic but different subjects that are not health students. They can also compare health and non-health students' knowledge regarding STIs.